2022
DOI: 10.1371/journal.pone.0276686
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of dental plaque with a 3D-intraoral-scanner—A tool for whole mouth planimetry

Abstract: Planimetry is a reliable method for detecting and monitoring plaque. Until now, this method has mainly been applied to conventional-camera images, which is difficult and time-consuming in relation to the entire dentition. Today, 3D-intraoral-scans are well suited for imaging the entire dentition and are therefore an efficient and feasible alternative. 3D-intraoral-scans have already proven successful for the quantification of plaque based on a plaque index. Therefore, aim of this study was to investigate wheth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
0
9
0
Order By: Relevance
“…Giese-Kraft et al (2022) compared images recorded using an intraoral camera and IOS after plaque staining on a monitor and reported that the results were very similar. Jung et al (2022) reported that the entire tooth surface could not be observed in the central image owing to the convexity of the tooth surface in the image acquired by the intraoral camera; however, the entire tooth surface could be visualized on the IOS image. Therefore, T A B L E 1 Subjects information and measurements data.…”
Section: Discussionmentioning
confidence: 99%
“…Giese-Kraft et al (2022) compared images recorded using an intraoral camera and IOS after plaque staining on a monitor and reported that the results were very similar. Jung et al (2022) reported that the entire tooth surface could not be observed in the central image owing to the convexity of the tooth surface in the image acquired by the intraoral camera; however, the entire tooth surface could be visualized on the IOS image. Therefore, T A B L E 1 Subjects information and measurements data.…”
Section: Discussionmentioning
confidence: 99%
“…Two of the analyzed studies aimed to investigate whether plaque can be reliably detected, quantified, and monitored on 3D models of dental arches acquired by intraoral scanners. In the first case [20], this was conducted by measuring the amount of plaque with planimetric measurements using appropriate especially designed software; in the second case [24], it was conducted by comparing visual assessments performed chairside and with the 3D model. In both cases, the IOS was proven to be an adequate tool for measuring plaque.…”
Section: Discussionmentioning
confidence: 99%
“…In other cases, specific software referring to the dental field was used, such as WearCompare (leedsdigitaldentistry.com, accessed on 20 June 2023) [63], a purpose-based software specifically produced to assess tooth wear; TRIOS Patient Monitoring (3Shape A/S, Copenhagen, Denmark), proprietary software from the same company that produces the TRIOS IOS, which allows the visual recording of changes over time; OrthoCAD (Cadent, Inc., San Jose, CA, USA), proprietary software from the same company that produces the iTero scanner, which allows the analysis of dental arch models, enabling measurements of the width of dental arches, such as in [22], where the authors evaluated the effect caused by removable appliances over a period of 10 months in children with malocclusion; and Maxilim software (V2.3.0, Medicim NV, Mechelen, Belgium), which is used to align the IOS models. Additionally, self-developed software was used to address specific needs, such as the evaluation of dental plaque in 3D models [20], the assessment of teeth [21], and the identification of structural and functional problems along with a carefully designed OCT hardware prototype [41].…”
Section: Three-dimensional Model Of Evaluation Softwarementioning
confidence: 99%
“…Moreover, the burden on the patient is low. Intraoral assessment using IOS has been reported in recent years [12,13] IOS, which can be color-coded, is used to assess the plaque adhesion status.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the detection of plaque-encrusted areas using an IOS may be useful as a new oral hygiene evaluation method. Reports on oral hygiene conditions evaluated using IOS have increased in number, indicating that the application of IOS for oral hygiene evaluation is expected to continue increasing [11][12][13]. However, the usefulness of IOS-based oral hygiene assessment in clinical practice has not been veri ed.…”
Section: Introductionmentioning
confidence: 99%